2018
DOI: 10.5505/tjtes.2018.50724
|View full text |Cite
|
Sign up to set email alerts
|

Mortality determiners for fall from height cases

Abstract: BACKGROUND:The aim of the present study was to investigate the role of body mass index (BMI) and trauma severity score systems on the mortality rates of patients undergoing surgery due to falls from height. METHODS:This retrospective study included 45 consecutive adult patients with multitrauma who were admitted and operated on due to a fall from height between January 2008 and December 2016. Patients were divided into mortality and recovery groups (n=10 and n=35, respectively). The groups were compared in ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 19 publications
0
7
1
Order By: Relevance
“…Some reports have found that fall height is not a factor aggravating the outcome of a fall from height injury 5 , 10 , but in our survey, as in other reports, we found that fall height was a significant factor 3 , 4 , 11 , 12 . The impact force is defined by mass (kg) × acceleration (m/s 2 ).…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…Some reports have found that fall height is not a factor aggravating the outcome of a fall from height injury 5 , 10 , but in our survey, as in other reports, we found that fall height was a significant factor 3 , 4 , 11 , 12 . The impact force is defined by mass (kg) × acceleration (m/s 2 ).…”
Section: Discussioncontrasting
confidence: 48%
“…Therefore, initially, the prognosis and ISS values seemed much worse for those with suicide attempts than for their counterparts. However, mitigating factors such as younger age, lower body weight, and a higher rate of impact on the lower limbs outweighed these aggravating factors and led to better ISS values and prognoses in patients who attempted suicide compared with those we expected 5 , 17 , 18 . Therefore, a suicide attempt was not deemed an aggravating or a prognostic factor with respect to the ISS.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…In this study, it was found that there was a statistically significant difference between low RTS and increased mortality. (11), also reported RTS statistically significant difference between low RTS and increased mortality. Similarly, (12) analyzed 1276 death trauma patients between 1995 and 2000 and showed that RTS could be used to predict mortality in trauma patients.…”
Section: Discussionmentioning
confidence: 81%
“…It was determined that there was at least one comorbid disease in 32.8% of the patients, 41.0% were intubated, 46.3% had enteral feeding, 4.5% needed hemodialysis, and 14.2% were ex. Median (min-max) values of some clinical and laboratory features of the patients were 14 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) for GKS, 26 for SAPS II, 6 (1-72) days for a stay in the intensive care unit, 1 (0-72) days for mechanical ventilation, 1 (0.00-7.90) mg / dL for creatinine, 3.4 (1.10-5.00) g / dL for albumin, 152 (65-380)mmol / L for Glucose (Table 1). It was found that mortality in trauma patients did not differ according to gender and age.…”
Section: Resultsmentioning
confidence: 99%